Тime in Russian Language Picture of the World (the Word-formation Approach) - HARUTYUNYAN, VERONIKA (Bulletin of Yerevan University H: Russian Philology, 2021)
The paper is devoted to the problem of reflection the category of time in Russian language. Characteristics of linguistic expressionof this category are considered at the all levels, particularly at the word-formative level.
Keywords: russian language picture of the world, time, meaning, word-formation